Performance simulation of broadband multimedia wireless networks simulation based on OPNET - Sameer Abdul-Sattar Lafta; Aktham Hasan Ali; Marwah M. Kareem; Yasser A. Hussein; Adnan H. Ali (Institute of Advanced Engineering and Science, 2020)
As the rapid growth of multimedia application over the Internet, it is essential to preserve the Quality of Service (QoS), which is certifying the guaranteed service through the Internet and representing the biggest challenges for the current IP based services. Multimedia traffic usage has been increased in relation to the streaming media such as video conferencing using OPNET, the performance can be simulated based on heavy and light scenarios for video conferencing including web traffic. The overall WLAN load data are obtained for such scenarios, also the performance of simulated overall Delay in the three scenario networks is measured.